(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the systematic processes of the reader’s creative activity in the problematic teaching of the physics section "Electrodynamics" in secondary schools are explained logically in a row, sequentially, in accordance with scientific and didactic principles.